Urinary tract infection with renal abscess (Indian Journal of Case Reports, 2024)
Renal abscess is very rare among intra-abdominal abscesses in children. Ascending infection is the most common cause in children compared to hematogenous spread in adults and Escherichia coli is the main pathogen. Persisting high-grade fever is an alarming sign to intervene and has to be taken care of. Here, we are presenting the case of a 3-year-old boy with Klebsiella urinary tract infection and E. coli renal abscess of 4 cm size. Contrast-enhanced computed tomography abdomen helped in early intervention and management. The child responded very well to parenteral antibiotics and ultrasound-guided percutaneous aspiration.